Influenza Research in the Eastern Mediterranean Region: A Review - Wasiq Khan (Oman Medical Journal, 2017)
Given the importance of influenza infections in the Eastern Mediterranean Region (EMR), we conducted a comprehensive literature review to analyze the status of influenza research in the region from 2012. Inﬂuenza research has gained more momentum recently with the emergence of H5N1 and new virus strains. Research covering epidemiological, veterinary, and basic science aspects is growing. More sequences were being generated per year, not only for diagnostic purposes but also for research. We included gray literature publications in our search and found several graduate student dissertations from Egypt, which were published on an online portal. However, the search revealed some weaknesses, mostly in the areas of study design and the lack of surveillance studies. Another weakness was the fact that the publications originated from very few countries, mainly Egypt and Iran. Although improving, influenza research in the EMR remains weak. We recommend encouraging countries in the EMR to conduct more influenza research using stronger methodologies.